Apakah Kemiskinan Itu Penderitaan? : Berteologi Bersama Pedagang Kaki Lima di Malang - Purnawan, Yohanes I Wayan (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2011)
The article argues that poverty does not always correspond to suffering. It depends very much on how people approach to or cope with their daily lives. People of the margins in the urbanized city of Malang - which is now and then not benevolent - could offer some insight to deepen our today's spirituality. Inspired by the Javanese rila-nrima-sabar (readiness-acceptance-patience) people could live their lives in a dynamic way beyond dissatisfactions or complaints. The so-called local genius correlates to theology of the cross in Christian tradition. The writer then reasons that suffering or the cross as part of life should be bravely addressed or confronted. Rila-nrima-sabar is human-divine capital which enables people to come out as winner. Christian spirituality describes it as per crucem ad lucem, through the cross the faithful reach enlightentment and resurrection.